Alternative community-based gardening and water banks for micronutrients intake among women in northern Ghana - Clement Kubreziga Kubuga (Dialogues in Health)
Objectives: Worldwide, women experience high prevalence of micronutrient deficiencies due to poor quality diets and elevated needs of the subpopulation. In Ghana, micronutrient deficiencies are pronounced in northern Ghana especially during the prolonged dry/lean season. This study aimed to investigate whether or not the results from an earlier pilot study to improve micronutrient intakes could be replicated through the entire dry season and to explore alternative and sustainable dry season gardening models to improve diet quality among women in northern Ghana. Methods: In this quasi-experimental study, the experimental design comprised an experimental community (n = 102) and a control community (n = 104). Participants in the experimental community were provided with wooden containers, soil water retention technology (SWRT) beds, and water reservoirs for vegetables production. Control community did not receive any of the above. Results: The pilot study's results were successfully replicated throughout the dry season: container and SWRT community-based gardening as alternative dry season farming models, improved diet quality among women during the dry/lean season. The proportion of women consuming non diverse diets declined by 41 % in the intervention group. Furthermore, community-based gardening was successfully supported by community-based water banks for five months. This finding offers a potential solution to the shortcomings of conventional irrigation systems in northern Ghana. Conclusion: Alternative community-based dry season gardening models can contribute to improve micronutrient intakes and nutrition security in northern Ghana. Though the results of this study are promising, it is recognized that more extensive research is necessary.